MEMILIH PEMIMPIN NON MUSLIM : APLIKASI TEORI NEGOTIATION KHALED M. ABOU EL FADL - Ihwan Sormin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This paper explains how the law elects non-Muslim leaders using the authoritative negotiation theory approach of Khaled M Abou El Fadl. This article is motivated by incidents that make surah al-Mā'idah verse 51 the basis for not being able to elect non-Muslim leaders. The methodology used in this study is to use a descriptive analysis method of literature by searching for data from books and libraries. The results of this study are that most interpreters use a conservative view in drawing legal conclusions from this verse, and they do not see the context when this law was derived. Therefore, the author proposes Khaled M Abou El Fadl's authoritative negotiation method to reinterpret the law on electing non-Muslim leaders. The writer's conclusion is that choosing a non-Muslim leader is permissible with certain conditions